Cardiac CT: non-coronary applications. Issue 1013 (17th March 2010) - Gopalan, Deepa; Raj, Vimal; Hoey, Edward T D
Abstract : Cardiac CT involves acquisition of high-quality ECG-gated dynamic images of the heart. ECG gating allows exquisite delineation of the coronary arteries, which are subjected to respiratory and cardiac motion. Cardiac CT has an established role in the assessment of coronary artery disease in selected patient groups and permits detailed assessment of cardiac and great vessel anatomy. The technique can also be used for a number of non-coronary applications including assessment of the pericardium, cardiac tumours and pulmonary veins. In this article, these applications are reviewed and the salient imaging findings across a range of structural cardiac disease illustrated.